Genetic distance as a predictor of heterosis in single cross hybrids of fodder maize (Zea mays L.) - S. Palaniyappan1, K. N. Ganesan1*, N. Manivannan2, V. Ravichandran3 and N. Senthil4 (Electronic Journal of Plant Breeding, 2023)
Assessment of genetic distance between parents and selection of diverse parents are extensively used in many crops. Current study focuses the importance of genetic distance assessed through SSR markers (GDMOL) and morphological traits (GDMOR) in 28 fodder maize inbred lines and its impact on heterotic expression in resultant 195 single cross fodder maize hybrids. While comparing the mean green fodder yield in top performing hybrids synthesised with parents of higher GDMOL and GDMOR, it is understood that the genetic distance had definite impact on yielding heterotic hybrids with superior green fodder yield. It is evident from identification of a single cross UMI 1200 X GETM 25 with parents of greater GDMOL and GDMOR and a cross N 66 X DM 12-4 with parents of higher GDMOR recorded greater green fodder yield and superior standard heterosis (20.88%). The correlation studies revealed significant positive association between higher GDMOL of parents and heterotic performance of hybrids for crude protein and desirable negative association with crude fibre, ADF and NDF.